Peran Kepemimpinan Pendidikan dalam Pengelolaan Sumber Daya Manusia di Sekolah Negeri dengan Kurikulum Nasional - Sabariah, Liena Marliana; Supendi, Pepen (Melati Institute, 2024)
Educational leadership plays an important role in human resource management in public schools that implement the national curriculum. This article analyzes how effective leadership affects human resource management, especially in the context of managing teachers as the primary educators. Through a field study of several public schools, this article identifies the challenges faced in implementing the national curriculum as well as strategies that can be applied to improve the quality of teaching and teachers' skills. The findings show that leadership based on good human resource management can improve the quality of education, although major challenges such as lack of continuous training and limited funding remain. The study also suggests that public schools maximize the use of technology in teacher professional development and involve various stakeholders to achieve more optimal educational success.